Efektivitas Edukasi Pencegahan Seks Bebas Menggunakan Media Leaflet terhadap Sikap Remaja di SMAN 1 Hu’u - Fitria Yulastini; Nurdahwati Nurdahwati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Premarital sexual behavior among adolescents remains a public health concern in Indonesia due to its potential contribution to unintended teenage pregnancies and other reproductive health problems. Evidence suggests that many adolescents have limited knowledge and awareness regarding the risks associated with premarital sexual behavior. This study aimed to determine the effectiveness of leaflet-based education on adolescents' attitudes toward the prevention of premarital sexual behavior. This study employed a quasi-experimental design with a one-group pretest–posttest approach. The study was conducted at SMAN 1 Hu’u in July 2023. A total of 50 tenth-grade students were selected using purposive sampling. Data were analyzed using the Wilcoxon signed-rank test. Before the educational intervention, most participants demonstrated negative attitudes toward the prevention of premarital sexual behavior (35 students; 70%). After the intervention, the majority showed positive attitudes (47 students; 94%). The mean attitude score increased by 23.46 points following the educational intervention. The results of the Wilcoxon test indicated a statistically significant difference in attitudes before and after the intervention (p < 0.001). These findings suggest that leaflet-based education is effective in improving adolescents' attitudes toward the prevention of premarital sexual behavior among tenth-grade students at SMAN 1 Hu’u.